The Shape of Water Stream Induces Differences in P300 and Alpha Oscillation - Kanayama, Noriaki; Mio, Shumpei; Yaita, Ryohei; Ohashi, Takahiro; Yamawaki, Shigeto (Frontiers in Human Neuroscience, 2020)
Touching is a fundamental human behavior used to evaluate objects in the external world. Many previous studies have used tactile stimulation to conduct psychological and psychophysiological experiments. However, most of these studies used solid material, not water stream, as an experimental stimulus. To investigate water perception, or to easily control the temperature of an experimental stimulus, it is important to be able to control the water stimulus. In this study, we investigated the usability of water as an experimental stimulus for EEG experiments and report the basic EEG response to water stimulus. We developed a tactile stimulation device using a water stream to study EEG responses, with the ability to control the stimulus onset timing. As stimuli, we selected two types of water stream, normal and soft, based on a psychological experiment to confirm a difference of subjective feeling induced by these water streams. We conducted a typical oddball task using the two different water streams and recorded EEG waveforms from 64 electrodes whilst participants touched the water streams. We calculated P300 at the Pz electrode, alpha asymmetry at the frontal electrodes, and alpha suppression at the parietal area. As a result, we observed typical P300 differentiation based on the stimulus proportion (target 20% and standard 80%). We observed weaker alpha suppression when participants touched the soft water stream compared to the normal shower. These results demonstrate the usability of water stream in psychophysiological studies and suggested that alpha suppression could be a candidate to evaluate comfort of water stream.